Implementasi Kebijakan Jaringan Pengaman Sosial Pada Peraturan Gubernur Bali Nomor 15 tahun 2020 Dalam Perspektif Merilee S. Grindle (Jurnal Nawala Politika, 2023)
This research discusses the Social Safety Net Policy (JPS) in Bali Governor Regulation Number 15 of 2020. The aim of this policy is to distribute social assistance to communities affected by Covid-19 to meet basic living needs such as food availability, education costs and other basic needs. This research uses Merilee S. Grindle's theory which examines policy implementation contextually and contextually. This type of research is qualitative using literature study. Research findings show that the implementation of this policy has been realized quite well, but there are problems such as the realization of social assistance to students is not optimal, their local agricultural products are still not absorbed in the social assistance distributed by the Bali Provincial Government, and problems with inaccurate social assistance data. The success or failure of implementing this policy is influenced by the interests, power, strategy of actors, and the characteristics of government institutions.